Golgi polarization effects on infiltration of mesenchymal stem cells into electrospun scaffolds by fluid shear stress: Analysis by confocal microscopy and Fourier transform infrared spectroscopy. Issue 7 (8th August 2016) - Kim, Min Sung; Lee, Mi Hee; Kwon, Byeong-Ju; Koo, Min-Ah; Seon, Gyeung Mi; Lee, Jong Ho; Han, Dong-Wook; Park, Jong-Chul
ABSTRACT: The polarization of the Golgi apparatus is an important phenomenon in the directional migration of many types of cells, including fluid shear stress enhanced infiltration of cells into scaffolds. Fourier transform infrared (FT-IR) spectroscopy would be a potential tool to study cell infiltration into scaffolds because this technique has simple, reproducible, non-destructive characteristics. Here, we investigated the effect of Golgi polarization on the directional migration and infiltration of human mesenchymal stem cells (hMSCs) into poly(lactic-co-glycolic acid) (PLGA) scaffolds by fluid shear stress. The cell infiltration into scaffolds by fluid shear stress was observed by immunofluorescence and FT-IR. 2 μM of Brefeldin A (BFA) inhibited the reorganization of Golgi polarization in hMSCs. The blocking of Golgi reorganization by BFA caused the suppression of directional migration and infiltration into PLGA scaffolds induced by 8 dyne/cm 2 of fluid shear stress condition. In this study, we investigated how Golgi polarization plays an important role in the directional migration and infiltration of hMSCs into scaffolds by responding to the fluid shear stress. The possibility of FT-IR to be a potential tool for analysis of cell infiltration into scaffolds was identified since the immunofluorescence data matched FT-IR data.